2011
DOI: 10.1039/c1fo10017c
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of milk-derived peptides in cardiovascular disease

Abstract: Bioactive peptides derived from milk proteins are of particular interest to the food industry due to the potential functional and physiological roles that they demonstrate, particularly in relation to cardiovascular disease (CVD). By 2020 it is estimated that heart disease and stroke will become the leading cause of death and disability worldwide. Acute and chronic cardiovascular events may result from alterations in the activity of the renin-angiotensin aldosterone system and activation of the coagulation cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 262 publications
0
82
0
4
Order By: Relevance
“…Food proteins derived from different plant and animal sources have demonstrated multifunctional physiological activities in disease prevention both in vitro and in vivo conditions. For instance, several studies have isolated bioactive peptides from plant sources including, pea , flax , sunflower (Ren, Zheng, Liu & Liu, 2010), soy proteins , rapeseed (Mäkinen, Johannson, Vegarud Gerd, Pihlava & Pihlanto, 2012), hemp seed , chickpea (Kou, Gao, Zhang, Wang & Wang, 2013), alfalfa (Xie, Huang, Xu & Jin, 2008a), wheat (Thewissen, Pauly, Celus, Brijs & Delcour, 2011), sweet potato and animal origin including egg (You, Udenigwe, Aluko & Wu, 2010), fish (Sampath Kumar, Nazeer & Jaiganesh, 2012), bovine lactoferrin (Ruiz-Giménez et al, 2012), tuna (Qian, Je & Kim, 2007), milk (Phelan & Kerins, 2011), shark liver (Huang & Wu, 2010), chicken bone (Cheng et al, 2008), cuttlefish (Balti et al, 2012), porcine skin (Hsu, Tung, Huang & Jao, 2013) and salmon (Ahn, Jeon, Kim & Je, 2012;Girgih, Udenigwe, Hasan, Gill & Aluko, 2013).…”
Section: List Of Tables Pagementioning
confidence: 99%
“…Food proteins derived from different plant and animal sources have demonstrated multifunctional physiological activities in disease prevention both in vitro and in vivo conditions. For instance, several studies have isolated bioactive peptides from plant sources including, pea , flax , sunflower (Ren, Zheng, Liu & Liu, 2010), soy proteins , rapeseed (Mäkinen, Johannson, Vegarud Gerd, Pihlava & Pihlanto, 2012), hemp seed , chickpea (Kou, Gao, Zhang, Wang & Wang, 2013), alfalfa (Xie, Huang, Xu & Jin, 2008a), wheat (Thewissen, Pauly, Celus, Brijs & Delcour, 2011), sweet potato and animal origin including egg (You, Udenigwe, Aluko & Wu, 2010), fish (Sampath Kumar, Nazeer & Jaiganesh, 2012), bovine lactoferrin (Ruiz-Giménez et al, 2012), tuna (Qian, Je & Kim, 2007), milk (Phelan & Kerins, 2011), shark liver (Huang & Wu, 2010), chicken bone (Cheng et al, 2008), cuttlefish (Balti et al, 2012), porcine skin (Hsu, Tung, Huang & Jao, 2013) and salmon (Ahn, Jeon, Kim & Je, 2012;Girgih, Udenigwe, Hasan, Gill & Aluko, 2013).…”
Section: List Of Tables Pagementioning
confidence: 99%
“…For both the C12-peptide and the bonito protein-derived peptide Leu-Lys-Pro-Asn-Met, it was concluded that a cause and effect relationship has not been established between the consumption of the peptides and maintenance of normal BP [128][129]. In the US, the Food and Drug Administration (FDA) assesses the scientific evidence for health claims under the 1990 Nutrition Labelling and Education Act [130] and the 1994 Dietary Supplement Health and Education Act [131].…”
Section: Hypotensive Peptides As Functional Food Ingredientsmentioning
confidence: 99%
“…In order to address this issue, the addition of γ-aminobutyric acid (GABA) 2,3) and angiotensin-convertingenzyme (ACE)-inhibitory peptides [4][5][6][7][8] to the pickles was studied. Such compounds exhibit antihypertensive effects and also have different blood pressure-reducing mechanisms.…”
mentioning
confidence: 99%